Context-sensitivity and context-productivity: notions of “practice” and “practicality” in ethnomethodology and conversation analysis - Meyer, Christian (Frontiers in Sociology, 2024)
The text reconstructs the concepts of practice and practicality used in ethnomethodology and conversation analysis and examines their internal similarities and differences as well as similarities and differences to other practice theories. After a description of the characteristics of practice theories, the ethnomethodological perspective on practice and practicality is presented. Then, the use of the terms in conversation analysis is examined. Ethnomethodology uses the notions of “practice” and “practicality” to outline a non-metaphysical theory of social order in which the sharedness of rules or meanings is not presupposed. “Practical” here means that social action, and social order more generally, are practically grounded as well as temporally and situationally constrained. The fact that practical action is fundamentally situated and can only be understood “from within” establishes an essentially indexical character of practical action. In conversation analysis, “practices” are viewed as “context-free” but “context-sensitive” components that constitute action and as such become the objects of investigation. While some have diagnosed a departure of conversation analysis from its ethnomethodological roots, I argue that “context-freeness” and “context-sensitivity” should be complemented by “context-productivity” by reference to Garfinkel’s interpretation of Aron Gurwitsch’s gestalt phenomenology in order to formulate a more encompassing concept of practice.